Effect of Experience Quality on Ethnic Restaurant Customer Loyalty: Mediating Role of Restaurant Image - Ananda Sabil Hussein; Eka Putri Rifandani (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
This study tests the relationship between experience quality, restaurant image, and customer loyalty in Indonesian ethnic restaurants. In addition, this study tests the mediating role of restaurant image in the relationship between experience quality and customer loyalty. Two hundred and five respondents participated in this study. This study employed PLS with smartPLS program to test the proposed research objectives. The findings indicated that service quality, food quality, and physical environment quality as dimensions of experience quality played essential roles in creating a positive restaurant image. Furthermore, this study found that restaurant image significantly affects customer loyalty. This study discovered the mediating functions of restaurant image in the relationship between experience quality dimensions and customer loyalty. Upon completing the research objectives, this study provides theoretical and practical contributions.